2016
DOI: 10.1161/circulationaha.116.023233
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipidomic Profiles Improve on Traditional Risk Factors for the Prediction of Cardiovascular Events in Type 2 Diabetes Mellitus

Abstract: URL: https://clinicaltrials.gov. Unique identifier: NCT00145925.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
212
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(231 citation statements)
references
References 43 publications
14
212
5
Order By: Relevance
“…65 Mass spectrometry has also shown that sphingolipids, phospholipids, cholesterol esters, and gylcerolipids are associated with an increased risk of adverse cardiovascular events in patients with diabetes mellitus. 66 High-throughput metabolite profiling by nuclear magnetic resonance spectroscopy has also identified a further 33 lipids and metabolites that are predictive of cardiovascular events, although only 4 metabolites showed independent risk of adverse cardiovascular events when routine lipids were adjusted for, phenylalanine and monounsaturated fatty acid levels were associated with increased risk whereas omega-6 fatty acids and docosahexaenoic acid were associated with decreased risk. 67 Novel lipid-related markers, including serum levels of proprotein convertase subtilisin/kexin type 9, 5 oxidized phospholipids, 68 and secretory phospholipase A 2 69 (Table 1), have also recently been shown to be associated with a risk of developing coronary artery disease in the general population.…”
Section: Lipidsmentioning
confidence: 99%
“…65 Mass spectrometry has also shown that sphingolipids, phospholipids, cholesterol esters, and gylcerolipids are associated with an increased risk of adverse cardiovascular events in patients with diabetes mellitus. 66 High-throughput metabolite profiling by nuclear magnetic resonance spectroscopy has also identified a further 33 lipids and metabolites that are predictive of cardiovascular events, although only 4 metabolites showed independent risk of adverse cardiovascular events when routine lipids were adjusted for, phenylalanine and monounsaturated fatty acid levels were associated with increased risk whereas omega-6 fatty acids and docosahexaenoic acid were associated with decreased risk. 67 Novel lipid-related markers, including serum levels of proprotein convertase subtilisin/kexin type 9, 5 oxidized phospholipids, 68 and secretory phospholipase A 2 69 (Table 1), have also recently been shown to be associated with a risk of developing coronary artery disease in the general population.…”
Section: Lipidsmentioning
confidence: 99%
“…General characteristics of the 12 selected articles are shown in Table . Half of the articles (6/12) were published in 2014, and all except 2 were conducted using European and/or US populations. These 12 articles include 19 separate primary discovery (or “learning”) and replication (or “validation”) analyses of metabolites in relation to CVD risk.…”
Section: Resultsmentioning
confidence: 99%
“…In 3 articles participants had a previous history of suspected coronary disease at baseline. Another article included older participants, of whom 68% had a prior history of CVD, and 2 articles included exclusively individuals with type 2 diabetes mellitus coupled with history of CVD or other CVD risk factors …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that are relevant to the topic have already been published, such as Alshehry et al[6], who found that sphingolipids, phospholipids, cholesterol esters and glycerolipids were associated with future cardiovascular events and cardiovascular death in people with type 2 diabetes mellitus; Zhang et al[7], identified various metabolomic biomarkers in patients with ovarian epithelial cancer; and De Oliveira et al[8], identified some lipids in greater abundance in the plasma of pregnant women in pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%